The history of peace-building in East Timor : the issues of international intervention / Katsumi Ishizuka. - Ishizuka, Katsumi (Foundation Books, 2010)
East Timor, (renamed Timor-Leste after independence in 2002) a small tropical country northwest of Australia, is one of the newest members of the United Nations. There are several reasons for East Timor having been in focus in international affairs. Firstly, it was its occupation by Indonesia and its brutal rule since 1975 and the countrys achievement of independence in 2002. Secondly, East Timor illustrates a case of realpolitik by the superpowers in international relations, as was evident from their support to Indonesia, or their complete indifference to the issue.